Designing a QR Code Model Examination System with the Zachman Framework - Irawan, Bei Harira; Prihadi, Deddy; Rahmatika, Dien Noviany; Nugroho, Catur; Soleman, Soleman; Tukino, Tukino; Hananto, April Lia; Silva, Tiago; Eichler, Luiz (Journal International of Lingua and Technology, 2023)
The Digital Business study program is a new study program within the Faculty of Economics and Business of Universitas Pancasakti Tegal where previously there were only 3 study programs, namely the Management, Accounting, and Taxation study programs. Every semester the Faculty of Economics and Business always holds Mid Semester Test (MST) and a Final Semester Test (FST), In both implementations, there are still queues of students who have already registered and paid for exams at the Front Office to take exam cards. This queue creates a large crowd at the Front Office and often causes the Administrative division that prints the cards and the Front Office staff to be overwhelmed in printing and distributing test cards to students. This study uses the Zachman Framework architectural model approach which is a framework in providing the basic organizational structure that supports access, integration, interpretation, development, management, and changes to the architectural devices of organizational information systems in the form of a matrix with a combination of planners and owners perspectives and the addition of two more perspectives. namely the perspective of the information system architecture which provides an overview of the design and architectural testing of the system as a novelty method.